2021
DOI: 10.1007/s10620-021-07084-1
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Update of Pancreatic Cysts

Abstract: CH Contrast-enhanced harmonic EUS-FNA Endoscopic ultrasound-guided fine needle aspiration LGD Low-grade dysplasia CEA Carcinoembryonic antigen AGA American Gastroenterological Association EUS-TTNFB EUS-guided through-the-needle forceps biopsy nCLE Needle confocal laser endomicroscopy QoL Quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…By inserting a micro-forceps device through a 19-gauge needle, this technique enhances tissue sampling of PCL and thus leads to a more definitive diagnosis and decrease in interobserver variability. 13 , 14 A recent study showed that EUS-TTNB has a higher diagnostic yield in the preoperative assessment of PCL than the combination of EUS-FNA cytology and fluid CEA. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inserting a micro-forceps device through a 19-gauge needle, this technique enhances tissue sampling of PCL and thus leads to a more definitive diagnosis and decrease in interobserver variability. 13 , 14 A recent study showed that EUS-TTNB has a higher diagnostic yield in the preoperative assessment of PCL than the combination of EUS-FNA cytology and fluid CEA. 15 …”
Section: Discussionmentioning
confidence: 99%
“…By inserting a micro-forceps device through a 19-gauge needle, this technique enhances tissue sampling of PCL and thus leads to a more definitive diagnosis and decrease in interobserver variability. 13,14 A recent study showed that EUS-TTNB has a higher diagnostic yield in the preoperative assessment of PCL than the combination of EUS-FNA cytology and fluid CEA. 15 Pancreatic neoplastic cysts can be subclassified into two categories: mucinous (intraductal papillary mucinous neoplasms, mucinous cystic neoplasms, and intraductal oncocytic papillary neoplasms) and non-mucinous (serous cystadenomas).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cystic lesions (PCLs) have a prevalence rate of 2.4% to 24.3% in the asymptomatic adult population [ 1 , 2 ]. Common PCLs consist of five main subtypes, and each presents different disease courses and aggressiveness: (1) intraductal papillary mucinous neoplasm (IPMN), (2) mucinous cystic neoplasm (MCN), (3) serous cystic neoplasm (SCN), (4) cystic neuroendocrine tumor (NET), and (5) pseudocysts [ 3 ]. Differentiation among subtypes of PCLs is critical, as mucinous PLCs have higher cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the fluid cytology has very low sensitivity, which often need the combination of methods to support the diagnosis. 1,4 The recent advances in EUS-like needle confocal laser endomicroscopy and through the needle biopsy (TTNB) sampling has led to an increase in appropriate characterization and diagnosis of the PCL. The ability to obtain tissue from the cystic wall or mural nodule by TTNB forceps can provide a histologic diagnosis for PCLs.…”
Section: Introductionmentioning
confidence: 99%